2001
DOI: 10.1074/jbc.m011369200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of UDP-GlcNAc:Lactosylceramide β1,3-N-Acetylglucosaminyltransferase (β3Gn-T5), an Essential Enzyme for the Expression of HNK-1 and Lewis X Epitopes on Glycolipids

Abstract: A new member of the UDP-N-acetylglucosamine:␤-galactose ␤1,3-N-acetylglucosaminyltransferase (␤3Gn-T) family having the ␤3Gn-T motifs was cloned from rat and human cDNA libraries and named ␤3Gn-T5 based on its position in a phylogenetic tree. We concluded that ␤3Gn-T5 is the most feasible candidate for lactotriaosylceramide (Lc 3 Cer) synthase, an important enzyme which plays a key role in the synthesis of lacto-or neolacto-series carbohydrate chains on glycolipids. ␤3Gn-T5 exhibited strong activity to transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
108
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 115 publications
(109 citation statements)
references
References 52 publications
1
108
0
Order By: Relevance
“…elongation of polylactosamine chains, however they exhibit a different substrate specificity dependent on the length of the polylactosamine chain [1,3]. Our in vitro analysis previously demonstrated that b3Gn-T2 is most active toward polylactosamine substrates having 2-5 LacNAc repeats [1].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…elongation of polylactosamine chains, however they exhibit a different substrate specificity dependent on the length of the polylactosamine chain [1,3]. Our in vitro analysis previously demonstrated that b3Gn-T2 is most active toward polylactosamine substrates having 2-5 LacNAc repeats [1].…”
Section: Introductionmentioning
confidence: 99%
“…Three b3-glycosyltransferase (b3-GT) motifs, XIRX(S/T)W(G/L/M), (F/Y)-XXXXDXD and (E/D)DVXXGX, which we found in a previous study, are commonly encoded in b3-GTs that combine two sugars with a b1,3-linkage [1][2][3][4]. These specific motifs are shared by b3Gal-Ts, b3GalNAc-Ts and b3Gn-Ts.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations